Description of two new Capnia species (Plecoptera: Capniidae) from the Hengduan Mountains of southwestern China - Chen, Zhi-Teng; Du, Yu-Zhou (Zootaxa, 2017)
Two new species of the genus Capnia from the Hengduan Mountains of southwestern China, C. oblata sp. nov. and C. xiei sp. nov. are described and illustrated as new members of the C. cordata Kimmins species group. Capnia oblata sp. nov. is characterized by posteromedial process of tergum 9 connecting antecosta with the medial sclerite bar. Capnia xiei sp. nov. is characterized by main epiproct sclerite bifurcate apically and basally with a bilamellar structure. The new species are compared with similar taxa.